Amnesty for Militants and Sustainable Peace in the Niger Delta Region of Nigeria - Tobi, Ariyo Andrew; Adesanmi, Fatai Olubunmi (NIU Journal of Social Sciences, 2020)
The objective of this study is to ascertain the extent to which the amnesty programme for the militants in the Niger Delta has stemmed the tide of restiveness in the region. The study relied on secondary data sourced from textbooks, journals and newspapers and employed relative deprivation theory as a framework of analysis. The findings showed that the amnesty programme for the militants was a child of necessity adopted by the Nigerian government to check the incessant acrimony in the Niger Delta region to stabilise oil production. On the one hand, the disarmament and demobilisation components of the programme to a large extent, reduced hostilities in the region. This trend led to an increase in oil production. On the other hand, contradictions inherent in the implementation of the programme particularly the reintegration of the ex-militants, suspension of the sponsorship of their education, the deployment of force by the government and failure of the policy to address issues of infrastructural development, environmental degradation, youth employment among others spurred fresh hostilities in the region. The study concluded that for the programme to be successful, reintegration efforts must be comprehensive, constant dialogue with all stakeholders  as well as meaningful infrastructural development in the region should be central in the agenda of the government. Keywords: Amnesty, Disarmament, Demobilisation, Militancy, Niger Delta, Peace-building, Reintegration